La producción pictórica en Almería: los centros de enseñanza artística (1850-1936) - Caparrós Masegosa, Lola (Cuadernos de arte de la Universidad de Granada, 1990)
The present study examines the centres of Education in the Fine Arts and prívate paíntíng schools in Almeria forrn the second half of the 19th to the first third of the 20th century. The author analyzes the role played by such institutions as motivating forces which stimulated the extraordinarily rich and fertile artistic activity in the town in the period under consideration, coming after a peculiarly sterile epoch. marked by widespread apathy.